Qualitative Study : Mother's Knowledge about Baby Gym at PMB Andina Palembang - Susmita Susmita; Bella Riska Ayu; Tri Restu Handayani (Journal of Educational Innovation and Public Health, 2025)
Aroun d 5 to 25% of children under the age of five experience motor development disorders and as many as 30% of babies show signs of motor delays. Stimulation can be given as a form of exercise therapy, which aims to improve and optimize body condition through continuous stimulation. One of the stimulations that can be done is baby gym. This study aims to analyze mothers' knowledge about baby gym in depth. This study uses a qualitative approach with an in-depth interview method. The subjects of the study or informants were mothers who had babies aged 0-12 months. The results of the study obtained knowledge Mother about baby gym part big nature general and not detailed. Only part small mothers who implement baby gym active For stimulate development motor baby. More education​ structured and access more information​ wide required For push mother to be able practicing baby gym with Correct.